Elevated gastrin‐releasing peptide receptor mRNA expression in buccal mucosa: Association with head and neck squamous cell carcinoma. Issue 2 (20th March 2012) - Egloff, Ann Marie; Liu, Xuwan; Davis, Autumn L. Gaither; Trevelline, Brian K.; Vuga, Marike; Siegfried, Jill M.; Grandis, Jennifer R.
Abstract Background Expression of gastrin‐releasing peptide receptor (GRPR) is elevated in mucosa adjacent to head and neck squamous cell carcinoma (HNSCC) compared with mucosa from cancer‐free controls, suggesting elevated GRPR expression may indicate presence of HNSCC. Methods We measured GRPR mRNA levels in histologically normal buccal mucosa from 65 surgical patients with HNSCC and 75 cancer‐free control subjects using quantitative polymerase chain reaction (PCR). We tested for association between GRPR expression and HNSCC and evaluated differences in patient progression‐free survival (PFS). Results Buccal GRPR expression was higher in cases but not controls who were active smokers (p = .04). High GRPR expression was associated with HNSCC (odds ratio [OR] = 3.55; 95% confidence interval [CI] = 1.15–10.93), even after adjustment for age, sex, tobacco use, and sample storage time. PFS did not differ between patients with HNSCC with high versus low GRPR expression (p = .22). Conclusion Elevated buccal GRPR expression was significantly associated with HNSCC independent of known risk factors but was not an indicator of disease prognosis. © 2012 Wiley Periodicals, Inc. Head Neck, 2013